Anesthesia Management in Intramural Uterine Myoma and Obesity Morbid Patients Who Underwent Myomectomy Perlaparatomy - RZ Harahap; Rose Mafiana (HM Publisher, 2020)
Introduction. Obesity is a condition that increases the challenges in the surgical process. Obesity increases the risk of sleep apnea and affects anaesthetics. This case report aims to discuss the management of anaesthesia in a patient with morbid obesity. Case. Female, 26 years old, with intramural uterine myoma and morbid obesity, will undergo myomectomy per laparotomy with ASA II physical status, performed anaesthesia with general anaesthesia intubation technique using the anaesthetic agent Propofol 1-2.5 mg/kg titration until the patient falls asleep, fentanyl 1-2 mcg/kg, then the patient was intubated in a ramped position with sleep non-apnea. After it was confirmed that the ETT was entered, 30 mg of a muscle relaxant (atracurium) was added. The operation lasts 1 hour 30 minutes, with a bleeding 250 cc, hemodynamically stable. Conclusion. Morbid obesity has extraordinary implications for anaesthetic management. Various considerations for patients with morbid obesity are needed starting from the preoperative, intraoperative, to postoperative periods. Regional anaesthesia is preferred because the physiological function of unhealthy obese patients is impaired due to excess body weight. Selection of anaesthetic agent and calculation of drug dose is crucial to know because there is a change in the volume of distribution. The pharmacokinetics of most general anaesthetics are affected by the adipose tissue mass, produce a prolonged drug effect, and less predictable.